2018
DOI: 10.1002/admt.201800299
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating 3D Structures by Combining 2D Printing and Relaxation of Strain

Abstract: materials to achieve extreme overhangs, and are limited by trade-offs between the speed of printing and the minimum feature sizes and surface roughness. [8,9] In contrast, "2D printing" techniques (such as digital printing and screen printing) are rapid, relatively inexpensive, and routinely achieve sub-millimeter feature sizes.Nature has also evolved the ability to form complex 3D structures (e.g., leaves, flowers, and tendrils) from initially quasiplanar structures. [10][11][12][13][14][15] These 2D to 3D tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…This is in sharp contrast to the actuated monotonic bending of pre‐strained soft actuators without changing their bending directions reported in previous studies. [ 13–14 ] The switch from monotonic positive bending to flip to negative curvature with the increase of p are well captured by the corresponding FEA simulations (Figure 3a,b, right).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…This is in sharp contrast to the actuated monotonic bending of pre‐strained soft actuators without changing their bending directions reported in previous studies. [ 13–14 ] The switch from monotonic positive bending to flip to negative curvature with the increase of p are well captured by the corresponding FEA simulations (Figure 3a,b, right).…”
Section: Resultssupporting
confidence: 54%
“…It shows that θ increases monotonically and nonlinearly with ε pre , which is consistent with previous studies on the bistrip soft actuators. [ 13–14 ] At the same applied ε pre , the actuators with a thicker pre‐stretched layer exhibit a larger bending angle than their counterparts due to their lower bending stiffness resistance of thin top layer. The disparity of θ between two counterparts increases dramatically with ε pre (Figure 2c), showing a dominant role of the bilayer thickness ratio h b / h t in manipulating the shape of pre‐curved 2D bending actuators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis also highlights the possibility to manufacture non-Euclidean elastic solids artificially, not only with a tailored pre-stress, but also with a particular stiffness distribution. Such solids can be designed to undergo specific elastic instabilities and to exhibit specific patterning in the technologically relevant conditions [79][80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present a design strategy to significantly increase the elastic strain energy stored by completely soft robots upon actuation, enabling their rapid and programmable actuation and recovery. Our work finds its foundations in previous approaches to create 3D structures using controlled buckling and selective bonding as a design principle and the work of Cafferty et al, who demonstrated the fabrication of soft grippers using a combination of direct‐ink printing and relaxation of strain. Complimentary to these works, we propose a strategy to exploit elastic energy storage to fabricate a variety of prestressed soft actuators (PSAs) by attaching a flexible but inextensible sheet (paper, textile, or plastic) to a prestressed elastomeric layer.…”
Section: Introductionmentioning
confidence: 93%